PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. KARANGMAS UNGGUL BEKASI - Aldika Rahmandana Saputra; Parwoto Parwoto (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
This study aims to analyze the effect of work motivation and job satisfaction on employee performance. The population in this study was 276 employees of PT. KarangMas Unggul (KMU) Bekasi. The sample used was 73 employees, calculated based on the Slovin formula. The sampling method uses proportional stratified random sampling. Data collection methods using survey methods, the research instrument is a questionnaire. Data analysis method uses Statistical Product and Service Solutions. This research proves that the effect of work motivation has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance.